The Nexus Between National Security Risks and Financial Market Stability: Evidence from Emerging Economies: Nexus Between National Security Risks and Financial Market Stability (Academic Journal of International University of Erbil, 2025)
Financial market stability in emerging economies is increasingly threatened by the rising complexity of national security risks. While economic indicators have long been studied as drivers of market behavior, recent global trends highlight the growing influence of political and digital threats on financial volatility. Among these, geopolitical tensions, terrorism, and cybersecurity breaches pose distinct and interconnected challenges to investor confidence and economic performance. Despite a growing body of research, the comparative impact of multiple security risks on market volatility remains underexplored, particularly in the context of structurally vulnerable emerging markets. Here we show that geopolitical risk is the most consistent and statistically significant driver of financial market volatility, while terrorism and cybersecurity incidents exert more episodic and context-specific effects.These findings are derived from panel regression models using data from 2013 to 2024 across emerging economies, supported by robustness checks and visual analyses. Unlike previous studies that focus on isolated threats, our results reveal that macroeconomic fundamental—especially GDP growth and FDI inflows—serve as important stabilizing forces, mitigating the disruptive effects of security risks. By integrating multiple dimensions of national security threats into a unified empirical framework, this study offers a clearer understanding of how political and digital instability affects financial systems. The results hold practical value for policymakers and investors seeking to develop resilient strategies in increasingly uncertain global environments.